9-cis and all-trans beta-carotene isomers of super critical CO2-extracted Dunaliella oil are absorbed and accumulated in mouse tissues. Issue 1 (1st January 2021) - Delman, Shahar; Anekstein, Mika; Afek, Arnon; Twitto-Greenberg, Rachel; Harats, Dror; Shnerb Ganor, Reut; Harari, Ayelet; Shaish, Aviv
ABSTRACT: Animals cannot produce β-carotene, and therefore they exclusively depend on its dietary availability. We previously showed that a 9-cis β-carotene-enriched diet, provided as Dunaliella powder, has a beneficial effect on atherosclerosis and diabetes mellitus in animal models and on lipid profiles, retinitis pigmentosa, and psoriasis in human trials. Therefore, the current study aimed to investigate the bioavailability of 9-cis β-carotene from super-critical CO2 -extracted Dunaliella oil in mice. In total, ten 12-week old mice were allocated into two groups: (1) a control-received unfortified diet; (2) a Dunaliella oil diet enriched with Dunaliella oil. Four-week dietary supplementation with Dunaliella oil led to a substantial accumulation of both all-trans and 9-cis β-carotene in the plasma, liver and white adipose tissue. β-carotene was stable in oil preparation, and the 9-cis to all-trans β-carotene ratio was constant (60:40, g/g) after two years of storage at 4°C. These results suggest that supercritically extracted Dunaliella oil can potentially be used as a food supplement.